An investigation on the consumption of over-the-counter medication among the population in Tirupati city - Yerramsetti Reshmasai; Gondi Surendra Kumar; Konda. N. V. S. R. P. L. Sailaja (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Non-prescription drugs/over the counter (OTC) drugs refer to all the drugs that can be legally purchased without requiring a prescription from a registered medical practitioner. The objectives of this study were to assess the sales of OTC drugs within pharmacies, to know the most widely consumed class of OTC drugs from pharmacies and to assess the awareness of the customers in asking about drug interactions while consuming OTC drugs in pharmacies. Methods: A cross-sectional study was conducted among pharmacies. The study period for data collection was 1 month, and for data analysis, 15 days were required. 50 pharmacies were randomly selected as the sample size. The questionnaire consists of 8 questions from which the most consumable class of drugs sold, and also during COVID-19 were identified. Results: Out of 50 pharmacies, 48% that is in 24 pharmacies the mostly sold class of OTC are drugs used for cold and cough / anti-histamines, 22% that is in 11 pharmacies the mostly sold class of OTC drugs are anti-pyretics / analgesics / anti-inflammatory compounds. In 2 pharmacies OTC drugs are mostly sold in summer season, in 24 pharmacies OTC drugs are mostly sold in winter season, in 4 pharmacies OTC drugs are mostly sold in monsoon season and in 20 pharmacies the OTC drugs are sold without any seasonal variation. Conclusions: The over the counter medication consumption was found to be high in Tirupati city because most of the results obtained in this study show similarity to the related studies. The most commonly sold drug among 50 pharmacies was drugs used for cold and cough /anti histamines and the sales of OTC drugs is also high in pharmacies of Tirupati.